The Influence of mass media on men and women's fitness attitude - Cervantes, Grace Lazaro 1976-
The study entitled "The Influence of Mass Media on Men and Women's Fitness Attitude," is an attempt to explore 1) men and women's usage of mass media, 2) their information sources regarding fitness, 3) the differences between male and female's fitness behavior and fitness attitude, and 4) the influence of mass media on their fitness attitude. A survey questionnaire was distributed among 100 males and females within the University of the Philippines-Diliman campus. The results of the study showed that males are more exposed to mass media that females. The findings claim that males, as well as females consider the different visual mass media, namely, television, newspaper and magazines, as sources which portray fitness. The findings of the study show that regardless of sex, diet is being practiced. And the kind of diet used by the majority is the low-food intake method. However, females diet primarily to lose weight while males consider it for health reasons. This survey of respondents aged 16-45 show that the top three reasons why males and females engage in physical activities are the following: first to improve one's body image, second is to have a well-toned and firm body, and third is so as to look good. This reveals that both males and females prioritize the psychological benefits of exercise more than it's physical benefits. Further analysis of the study reveals that as compared to males, females are more influenced by the media's portrayal of fitness. It showed that women, as compared to males are more concerned with their weight and body image.